AN ANALYSIS OF NATURALNESS IN THE INDONESIAN TRANSLATION OF GREEK TALE "TROJAN WAR"(The study of Indonesian translation of a tale that is intended for children) - Haris Fitria Gilang, - (2008)
The paper entitled AN ANALYSIS OF NATURALNESS IN THE INDONESIAN TRANSLATION OF GREEK TALE "TROJAN WAR" (The study of Indonesian translation of a tale that is intended for children) elaborates the readability grade of the text, the translation procedures that were used and the quality aspects in terms of accuracy, clarity, and naturalness. The writer worked with the descriptive method to describe the research. The data were collected from the book entitled "Famous Tales Retold Trojan War Parody Series" which is published by Nexx Media Inc. Bandung, Indonesia. The writer also carried the research by using the random sampling method to select a hundred samples from the population. The result showed that the text had grade five in Fry Readability Formula. Based on the result, the text was more suitable for the age in early childhood who had literacy ability well (seven and above). Besides, the text did not have very short words and sentences to be read by ages in the early childhood who did not have literacy ability well (age 3-6). Some translation procedures were used by the translator, but he/she did not play the role of the translator to produce the natural translation for the whole translation text.